DFT-1/2 method applied to 2D topological insulators: fluorinated and hydrogenated group-IV honeycomb systems. (17th August 2021) - Matusalem, Filipe; Bechstedt, Friedhelm; Guilhon, Ivan; Marques, Marcelo; Teles, Lara K
Abstract: We present a computationally efficient and accurate methodology to compute Z 2 topological invariants for systems without inversion symmetry including quasiparticle (QP) effects within the density functional theory (DFT)-1/2 method. The Wannier charge center evolution is applied to compute the Z 2 topological invariant and investigate the topological properties of group-IV graphene-like systems, graphene, silicene, germanene and stanene, whose inversion symmetry is broken by simultaneous functionalization with hydrogen and fluorine atoms. Different atomic arrangements are studied. The systems are stable with cohesive energy decreasing along the row from carbon to tin. A similar trend is observed for band gaps. The resulting topological invariants are compared with values obtained within conventional DFT and using a hybrid exchange–correlation functional. The variation of the results with the treatment of exchange and correlation demonstrates the importance of QP corrections for the prediction of the topological or trivial character.